2020
DOI: 10.1038/s41467-020-18443-3
|View full text |Cite
|
Sign up to set email alerts
|

Indirect regulation of HMGB1 release by gasdermin D

Abstract: The protein high-mobility group box 1 (HMGB1) is released into the extracellular space in response to many inflammatory stimuli, where it is a potent signaling molecule. Although research has focused on downstream HMGB1 signaling, the means by which HMGB1 exits the cell is controversial. Here we demonstrate that HMGB1 is not released from bone marrow-derived macrophages (BMDM) after lipopolysaccharide (LPS) treatment. We also explore whether HMGB1 is released via the pore-forming protein gasdermin D after infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 60 publications
1
101
0
Order By: Relevance
“…In the spiral ligament, we found that the tendency of AFD elevated ( Figures 3C,D ), which was consistent with the change in the total cochlear level of HMGB1 ( Figure 1B ). Necroptosis-, ferroptosis-, apoptosis- and pyroptosis-mediated mechanism have all been implicated in HMGB1 release from cells ( Scaffidi et al, 2002 ; Bell et al, 2006 ; Murai et al, 2018 ; Wen et al, 2019 ; Volchuk et al, 2020 ). Specifically, as a marker of cellular damage, the increasing HMGB1 level or the release of HMGB1 in the spiral ligament indicated the activation of cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the spiral ligament, we found that the tendency of AFD elevated ( Figures 3C,D ), which was consistent with the change in the total cochlear level of HMGB1 ( Figure 1B ). Necroptosis-, ferroptosis-, apoptosis- and pyroptosis-mediated mechanism have all been implicated in HMGB1 release from cells ( Scaffidi et al, 2002 ; Bell et al, 2006 ; Murai et al, 2018 ; Wen et al, 2019 ; Volchuk et al, 2020 ). Specifically, as a marker of cellular damage, the increasing HMGB1 level or the release of HMGB1 in the spiral ligament indicated the activation of cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 113 In more advanced stages, GSDMD pores lead to membrane destabilization and cell lysis, enabling the release of DAMPs such as HMGB1 that are too large to escape the cell through the pores. 114 Adding to the complexity of pyroptosis, several additional caspases are implicated in a noncanonical pathway, directly targeting GSDMD for cleavage. Murine caspase-11 was first described as a caspase-1 interactor more than two decades ago.…”
Section: Pyroptosis: a Master Regulator Of Inflammationmentioning
confidence: 99%
“…It is worth noting that there was some residual IL-1β release and pyroptosis even in Gsdmd -/- ; Gsdme -/- BMDMs, suggesting that another GSDMD and GSDME independent inflammation pathway can be activated downstream of NLRP3, potentially involving another caspase and/or another gasdermin. From our study it remains uncertain whether cytokines are secreted through GSDME pores in the setting of caspase-1 or GSDMD deficiency or are passively released when the cell membrane is grossly disrupted and LDH is released, as was recently proposed for in vitro GSDMD-mediated HMGB1 release 71 . Taken together, these results suggest that macrophages have more than one salvage mechanism to ensure that signals transmitted by inflammasome activators result in inflammation.…”
Section: Discussionmentioning
confidence: 84%